Hepatoprotective Effect of the Aqueous Extract of Camellia sinensis Against Methotrexate-induced Liver Damage in Rats - H. Jwied, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2017)
Methotrexate (MTX) is a folate antagonist widely used in the treatment of neoplastic diseases; its biotransformation in the liver produced active metabolites that promote hepatotoxicity. The present study was designed to evaluate the hepatoprotective effect of aqueous extract of Camellia sinensis (Green tea) against MTX-induced liver damage in rats. A model of liver injury in rats was induced by intraperitoneal injection of 20mg/kg MTX as a single dose followed by saline and 1.25% and 2.5% aqueous extract of green tea (GTE) were orally administered 7 days prior and 5 days after MTX-intoxication as a sole source of drinking water. After killing the animals, blood samples were obtained for evaluation of serum levels of alanine and aspartate aminotransferases (ALT and AST) and alkaline phosphatase (ALP) activities, while liver tissue homogenate was prepared to evaluate tissue levels of glutathione (GSH) and malondialdehyde (MDA). Additionally, liver tissue sections were prepared and stained with hematoxylin and eiosin for histological evaluation. The results showed that administration of green tea extract (GTE) significantly decreased the elevated levels of ALT, AST and ALP activities in the serum compared to MTX-treated group. Treatment of animals with GTE 7 days before and 5 days after MTX also elevates GSH levels and decreases MDA levels significantly compared to MTX-treated group, this was associated with improving histological features that already impaired due to exposure to MTX. In conclusion, treatment of rats with GTE protects hepatic tissue against MTX-induced liver damage in dose dependent manner.Key words: Green tea, Hepatotoxicity